The Scientific Research of Agriculture Accounting in Lithuania - Bružauskas, Valentinas; Zinkevičienė, Danutė (Ekonomika, 2005)
The article reveals the most important results of the research, which focuses on Agriculture accounting in Lithuania in the period of Soviet times and the regaining of Independence. In the article the results are linked with the latest requirement. Also the problems that should be solved in future are indicated.He research of this kind got its background under the conditions of Soviet centralized planned economy. Hence, the most important research results of this period are:1) improved methods of Production Cost Accounting;2) accounting methods prepared and applied to the needs of local and operating management, investigated possibilities of how to apply the method of fixed production standard cost;3) given suggestion how to improve accounting of fixed assets and indivisible funds;4) improved accounting technology of mechanization and automation;5) farmed new accounting documents and registers;6) improved methods of how to analyze the effectiveness of Production cost and fixed Asset.At the regaining Independence, scientific and applied researches were carried out in order to strengthen the informative function of Accounting. The researches were due to the reformation of the Accounting System. In this period, the following important means of accounting were formed and implemented:1) theory on new Financial statements;2) methods of family farm’s ordinary accounting double entry bookkeeping;3) Business Accounting Standard “Biological Asset”;4) new Charts of accounts concerning agricultural enterprises and family farms;5) new calculation methods of agriculture production costs;6) new material on accounting documents and registers.The analysis of the research results helped to reveal the problems that should be further solved. The most important ones are:1) to apply Business Accounting Standards to the Accounting of Agricultural Enterprises;2) to enlarge of informative and operative aspects of financial statements;3) to make the method of family farm double entry accounting less complicated;4) to develop the estimation of long term assets and inventories;5) to solve the problems of management accounting;6) to make the primary accounting less complicated;7) to develop computerized account